Kinesiology tape does not promote vertical jumping performance: A deceptive crossover trial. (February 2016) - Cheung, R.T.H.; Yau, Q.K.C.; Wong, K.; Lau, P.; So, A.; Chan, N.; Kwok, C.; Poon, K.Y.; Yung, P.S.H.
Abstract: Background: Kinesiology tape (KINTAPE) is one of the most common adhesive therapeutic tapes. Apart from clinical applications, KINTAPE claims to be able to enhance functional performance by muscle activity facilitation. However, emerging evidence suggests that the isokinetic muscle strength remains similar when the placebo effect is eliminated. Objectives: In view of the weak relationship between functional performance and isokinetic muscle strength, this study investigated the true effects of KINTAPE on functional performance. Design: Deceptive, randomized, and crossover trial. Method: Sixty four experienced volleyball players performed vertical jumping test under three taping conditions: true facilitative KINTAPE, sham KINTAPE, and no KINTAPE. Under the pretense of applying adhesive muscle sensors, KINTAPE was applied to their quadriceps and gastrocnemius in the first two conditions. Mean maximum jump height and peak jump power were averaged from three attempts. Within-subject comparisons were conducted by repeated measure ANOVA. Results: Out of 64 participants, 30 of them were successfully deceived and they were ignorant about KINTAPE. No significant differences were found in both maximum jump height (η 2  = 0.001; p = 0.241) and peak jump power (η 2  = 0.001; p = 0.134) between three taping conditions. Conclusions: The results showed that KINTAPE did not facilitate muscle performance by generating higher jumping power or yielding a better jumping performance. These findings reinforce that previously reported muscle facilitatory effects or functional enhancement using KINTAPE may be attributed to placebo effects. Highlights: This study examined the true effect of kinesiology tape on functional performance. Tape application did not promote vertical jump height or jump power in volleyball players. Kinesiology tape should not be considered for performance enhancement. These findings are based on athletes without injury and immediate effects only.